Amfory na wino z Hispanii Tarraconensis jako świadectwo handlu w zachodniej części basenu morza śródziemnego od I w. p.n.e. do I połowy II w. n.e. - Góralczyk, Agnieszka (Studia Europaea Gnesnensia, 2015)
During the period of the Republic, the viniculture of the Pyrenean Peninsula supplied wine for the local needs. When Rome had become Empire, wine production grew to a massive scale, which is attested to by numerous discoveries of amphorae from Spain both in Hispania Tarraconensis and other provinces in the western Mediterranean. In the 1st cent. AD, Spanish wine monopolised the market in the region. Towards the end of the 1st cent. AD, agricultural production in Hispania Tarraconensis was reorganised – vine was replaced with cereal. The early 2nd cent. AD saw discontinuation of business in most centres of ceramic production and disappearance of Roman villas whose main profits came from vineyards.